Effect of High Temperature on Swellable Organically Modified Silica (SOMS) and Its Application for Preferential CO Oxidation in H2 Rich Environment. Issue 14 (12th May 2020) - Basu, Dishari; Ailawar, Saurabh; Celik, Gokhan; Edmiston, Paul; Ozkan, Umit S.
Abstract: Transition metal oxide catalysts tend to deactivate in the presence of moisture during hydrogen purification using preferential oxidation (PROX) of carbon monoxide (CO) . Thus, novel water‐tolerant catalysts need to be developed. Herein, the evolution of heat treated swellable organically‐modified silica (SOMS), a hydrophobic organic‐inorganic hybrid material, has been characterized and applied as a catalyst support for PROX under moisture‐rich conditions. While the SOMS‐supported cobalt manganese oxide was found to be inactive, drastic improvement in CO conversion was observed for heat treated SOMS (HSOMS) supported catalysts. From thermogravimetric analysis and NMR spectroscopy it was found that SOMS retains its structural properties and hydrophobicity up to 400 °C. The performance of these catalysts was improved upon using toluene as the impregnation solvent, which enhanced the support wettability and improved active site deposition. The catalyst supported on HSOMS‐400 was found to be more water tolerant than a silica‐supported catalyst due to Si−O−Si(CH3 )3 groups retained from hexamethyldisilazane (HMDS) derivatization of SOMS. Abstract : Water tolerant catalytic support : A novel swellable and hydrophobic material known as Swellable Organically Modified Silica (SOMS) was heat treated to expand its pore structure and characterized extensively. These materials were then used to support cobalt manganese oxide sites, using different impregnation solvents, to protect them from moisture during the preferential oxidation of CO.